Serotype Features of 17 Suspected Cases of Foodborne Botulism in China 2019–2022 Revealed by a Multiplex Immuno-Endopep-MS Method - Wang, Jiang; Xu, Hua; Zhang, Cheng; Chen, Jia; Wang, Chunyan; Li, Xinying; Zhang, Yajiao; Xie, Jianwei (Frontiers in Microbiology, 2022)
Diagnosis of botulism caused by multiple serotypes of botulinum neurotoxin (BoNT) is still a challenge due to the lack of a reliable detection method. The present study develops a feasible laboratorial method based on an isotope dilution Immuno-Endopep-MS to detect BoNTs and determine their serotypes and activities in clinical samples. Eleven positive foodborne botulism cases out of a total of 17 suspected cases in China, 2019-2022 were determined by the established method. Blood, urine, vomitus, gastric mucosa samples and food samples were employed and evidenced to be suitable for the detection. Results showed that although single type A-intoxication was still the first cause among these foodborne botulism cases, other causes involving type E, type B and their mixed types were also determined, providing a glimpse to the serotype profile of botulism happened in recent years in China. Furthermore, in order to provide insights into in vivo profiles of toxin serotypes, a comprehensive analysis of clinical specimens collected from one family of four patients was performed during a clinically and therapeutically relevant timeframe. Serotypes and concentrations of BoNT in specimens revealed a good correlation with symptoms and progresses of disease. Additionally, serum was proved to be more suitable for detection BoNT/A with a detection window up to 12 days. Urine sample, although rarely reported for foodborne botulism diagnosis, was validated to be suitable for testing BoNTs with a longer detection window up to 25 days. To the best of our knowledge, this is the first comprehensive analytical research on in vivo profiles of serotypes A, B and E in different types of specimens from mixed botulism cases. Our method and findings facilitate the toxin detection and identification by clinical diagnostic laboratories.